PERUBAHAN KONSUMSI PANGAN DAN ASUPAN VITAMIN A IBU MENYUSUI SESAAT DAN TIGA BULAN SETELAH MELAHIRKAN Changes in Food Consumption and Vitamin A Intake of Breastfeeding Mothers in Moment and Three Months After Giving Birth - Abdul Salam; Dodik Briawan; Drajat Martianto; Abdul Razak Thaha (Media Gizi Indonesia, 2020)
Adequate intake of vitamin A during lactation is very crucial due to its eff ect on retinol levels in breast milk. This study was aimed to analyze the changes in food consumption and vitamin A intake of lactating mothers in moment and three months after giving birth. This study used a cohort design for 3 months involving 295 breastfeeding mothers. Subjects were selected according to inclusion criteria including mother with normal labour and full term month normally and term, have a baby with normal birth weight, and maximum of a third parity. A 2x24 hour food recall questionnaire was used to determine nutrient intake and a food frequency questionnaire to determine the consumption habits of sources of vitamin A. The Wilcoxon test and paired t test were used in this study. The results of study showed that the most frequently consumed vegetables both shortly and three months after childbirth were tomatoes, 65% and 73.9% respectively. Most frequently consumed fruits were mangoes, 18.3% and 13.6%. While the most frequently consumed animal source foods were eggs, 68.1% and 79.7%, respectively. Among the consumption of vitamin A sources foods, only the consumption of tomatoes, milk, and cooking oil were found increase signifi cantly in three months after delivery (p <0.05). The mean of protein, zinc and iron intake adequacy level were decrease signifi cantly in three months after delivery (p<0.05), but not with fat and vitamin A intake (p>0.05). It is necessary to increase the consumption of vitamin A food sources, especially during lactation to increase the content of vitamin A in breast milk to meet the needs of newborns and prevent vitamin A defi ciency both in mother and baby